Response of chlorophyll, morphology, and yield of several East Java superior soybean (Glycine max L.) varieties to levels of salinity - Tarigan, Puji Lestari; Moeljani, Ida Retno; Suryandika, Fadila; Munarko, Hadi (Universitas Padjadjaran, 2026)
Soybean production has been extended to saline areas. This development is a strategy to expand planting areas to suboptimal land to increase worldwide production. To support cultivation in these locations, it is necessary to develop superior varieties that are resistant to salinity and provide supporting technological inputs. In saline conditions, soybeans may face stress that leads to morphological, physiological, and yield disturbances. Consequently, the response of several soybeans in East Java should be observed. This study is a pot experiment and arranged in a Factorial Completely Randomized Design (CRD) consisting of two factors, soybean varieties and NaCl concentrations. The treatments comprise several NaCl levels: 0 g/L (non-saline), 5 g/L (moderate salinity), 15 g/L (high salinity), and 25 g/L (very high salinity). The observation used several parameters: chlorophyll content, plant height, leaf number, flowering time, pod forming time, number of pods, number of seeds, weight of 100 seeds, and harvest time. The soybean varieties used were Anjasmoro, Wilis, Dering 1, and Dering 3. Anjasmoro was identified as the soybean variety most tolerant to salinity stress based on chlorophyll content, morphology, and yield.